Analysis and overview of NQF level descriptors in European countries - (:unkn) unknown (Publications Office of the European Union, 2013)
Most of the 36 countries involved in implementing the European qualifications framework (EQF) have now (spring 2013) defined, and largely adopted, level descriptors of learning outcomes. They define what is meant by learning outcomes, describing what an individual is expected to know, be able to do and understand, having acquired a qualification at a particular level. "The analysis illustrates the influence of the EQF on national level descriptors, but it also demonstrates how countries have adjusted and further developed the learning outcomes approach according to national needs and priorities. National level descriptors have mostly been developed through extensive dialogue between different stakeholders (government, social partners, and education and training providers). This report supports EQF implementation and feeds directly into the referencing process, in which countries relate their national qualifications levels to the EQF. It also provides input into continuing evaluation of the EQF, to be concluded by a report of the European Commission to the European Parliament and Council later in 2013." (Hrsg., BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; G 2.5.3 Anschlussfähigkeit von Bildungsgängen; I 2.2 Europa; EU-Bildungspolitik; Nationaler Qualifikationsrahmen; Europäischer Qualifikationsrahmen; Europäische Union; Kroatien; Mazedonien; Montenegro; Schweiz; Serbien; Türkei; Island; Liechtenstein; Norwegen